Evaluation of the Radiopacity of Luting Cements by Digital Radiography. Issue 4 (25th October 2012) - Altintas, Subutay Han; Yildirim, Tahsin; Kayipmaz, Saadettin; Usumez, Aslihan
Abstract Purpose The aim of this study was to evaluate the radiopacity of eight contemporary luting cements using direct digital radiography. Materials and Methods Ten specimens, (5 mm diameter, 1 mm high) were prepared for each material tested (RelyX ARC, RelyX U100, RelyX Unicem, Nexus 2, Nexus 3, Metacem, Breeze, Adhesor zinc phosphate). The specimens were stored in a moist chamber at 37°C until completely set, then radiographed using a Kodak digital sensor and an aluminum step wedge with variable thicknesses (1 to 13 mm in 1‐mm increments) used for reference. A Kodak 2100 intraoral X‐ray unit was operated at 60 kV, 7 mA, and 0.20 seconds. According to international standards, the radiopacity of the specimens was compared with that of the aluminum step wedge using the equal‐density area tool of the Kodak Dental Imaging software (ver. 6.7). Data were analyzed by ANOVA and Tukey's test. Results Adhesor zinc phosphate cement showed the highest radiopacity of all materials and dentin. Breeze showed the lowest radiopacity (p < 0.05). No significant difference in radiopacity was observed between dentin and RelyX ARC, Nexus 2, or Metacem (p > 0.05). The radiopacities of Nexus 3 and RelyX Unicem were significantly higher than those of other resin cements and dentin (p < 0.05). Conclusions All materials showed radiopacity above the minimum recommended by the International Organization for Standardization and the American National Standards/American Dental Association. Breeze had less radiopacity than dentin.